Aerial View of Fresno - Watkins, Howard::::::::: (1983)
Aerial view of freeway 41 and Blackstone's ramps to 41; Fresno Air Terminal runways at top; no eastbound 180 construction yet Shows Roosevelt High and Valley Medical Center campuses, north half of fairgrounds